Data-Driven Analysis of Husband Support and Psychological Anxiety in Pregnant Women Using Educational Health Analytics - Imella Annisah; Sania Ihroma; Anggarani Prihatiningsih; Irvan Arivianto; Arsita Pratiwi (International Transactions on Education Technology (ITEE), 2026)
This study examines the relationship between husband support and psycholog- ical anxiety among pregnant women using a data-driven educational health ana- lytics approach. A cross-sectional quantitative design was employed at Pratama Suradita Clinic, Tangerang Regency, Indonesia. The sample consisted of 85 pregnant women selected from a target sample of 88 respondents using Slovin’s formula; three questionnaires were excluded due to incomplete responses. Psy- chological anxiety was measured using the Hamilton Anxiety Rating Scale (HARS), while husband support was assessed through a structured questionnaire covering emotional, informational, instrumental, and appraisal support. Instru- ment validity and reliability were confirmed prior to data collection (Cronbach’s alpha> 0.70). Chi-square analysis showed a statistically significant relation- ship between husband support and anxiety (p = 0.001). Pregnant women receiv- ing adequate husband support had an 88.1% lower probability of experiencing anxiety (OR = 0.119). These findings highlight the importance of involving husbands in prenatal educational programs to improve maternal mental health.